Laminated roof glazing for automobile
By using a combination of transparent glass sheet, infrared reflective stack, PVB interlayer and colorant polymer layer in automotive assembly glass, the high and complex problems of automobile assembly glass in the prior art are solved, and low light transmittance is achieved and low emissivity targets improve sun control performance and visual comfort.
Patent Information
- Application Number
- CN202380040929.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-16
- Filing Date
- 2023-05-11
- Publication Date
- 2024-12-27
AI Technical Summary
Existing automotive assembly glass has high cost, complexity and cannot effectively achieve the tradeoffs between low light transmittance and low emissivity in terms of sunlight control and thermal management, especially in roof applications, which lead to overheating in the vehicle.
The laminated assembly glass structure consisting of transparent glass sheets, infrared reflective stacks, PVB interlayers and colorant polymer layers is adopted to control the transmission of solar energy and visible light through the infrared reflective stacks and colorant polymer layers to achieve low transmission. Objects with light rate and low emissivity.
Achieve low-cost, low-complexity automotive-assembled glass with low light transmittance (less than 10%) and low total solar transmittance (less than 20%) while providing good sun control performance and visual comfort, reducing the car Internal temperature.
Smart Images

Figure CN119212864A_ABST
Abstract
Description
[0001] The present invention relates to a glazing for a motor vehicle, and in particular to a glazing used as a roof glass of a motor vehicle.
[0002] Glazing used as a panoramic roof or fixed roof in a vehicle must comply with a number of standards regarding heating of the vehicle interior when exposed to strong sunlight:
[0003] - on the one hand, not allowing all incident solar radiation to pass, so as not to overheat the vehicle interior and / or to limit energy consumption (e.g. excessive use of air conditioning due to the amount of heat entering the passenger cabin), and
[0004] - On the other hand, let in a minimum amount of light to fully illuminate the interior space and ensure minimum external visibility to maintain visual comfort and a cozy feeling.
[0005] Furthermore, meeting these two requirements - namely preventing excessive energy ingress and providing adequate lighting for the interior space - is necessarily a compromise. Therefore, laminated glass is required that offers an optimal compromise in terms of heat reflection while maintaining a certain light transmission.
[0006] Reducing CO2 emissions is a major challenge for industry today. For example, in the context of CO2 energy conservation, the US Federal Regulations (CFR, https: / / www.law.cornell.edu / cfr / text / 40 / 86.1869-12) grant CO2 credits to automakers in NAFTA markets for non-recycled CO2 reduction technologies, especially involving IR reflective coatings or heat absorbing glass. For example, panoramic sunroof glazing has an outer surface that is highly exposed to direct sunlight, which will cause heat and glare if the glass body is not coated or tinted.
[0007] The technical purpose of the invention is to limit glare by reducing light transmission through the glass and also to improve solar control properties in automotive glazing and in particular when used as a roof, thereby avoiding heating of the interior space of the passenger cabin, in particular in hot outdoor conditions.
[0008] To assess heat transfer through laminated glazing, the total solar transmittance (TTS) is usually measured using convention "A" AM 1.5 according to ISO 13837. Solar control performance is therefore measured by the total transmitted solar energy (TTS) of this type of glazing.
[0009] For example, to assess the light transmission through glazing in the visible range (380-780 nm), the T measured according to standard ISO 9050 (2003) may be used. L Light transmittance.
[0010] T LIt can be reduced by absorption. According to current technology, absorption is achieved by using body-tinted glass sheets in the glazing or, alternatively or additionally, by using one or more tinted PVB layers in laminated glazing (i.e. glazing made of several glass sheets joined together). However, such designs lead to overheating of the glazing.
[0011] Another important factor regarding solar control glazing and its ability to prevent internal heating is its ability to reflect infrared radiation. Typically, this ability is achieved by a stack of thin layers (i.e. of the order of a few nanometers or tens of nanometers in thickness), one of which has a high reflectivity in the infrared. This ability is typically obtained by a stack comprising at least one and preferably two or even three silver layers of a few nanometers thick separated by layers of dielectric material, in particular of the type described in applications WO 2005 / 051858 or WI 2013 / 104439, to which reference is made for further details of such stacks.
[0012] For example, the total emissivity ε at normal incidence measured according to standard NF EN 12898 (2001) is n It is used to measure the ability of glazing with such a stack to reflect infrared light. n The lower it is, the more infrared light is reflected by the glazing.
[0013] To meet the above objectives, several configurations of laminate structures have been described.
[0014] According to a first possibility, it is known from publication WO 2006 / 108980 A2 to use tinted lenses which absorb part of the radiation and filter out a large part of the incident radiation spectrum, without distinguishing between the different parts of the solar spectrum (UV-visible-near IR).
[0015] According to another possible construction, it has been proposed to use a colored interlayer, in particular a colored PVB (polyvinyl butyral) film, which bonds two glass sheets (optionally also colored). For an example of such a construction, see also EP 0 687 554 A1.
[0016] The specification of patent US Pat. No. 6,910,729 instead describes a thermal comfort glazing system combining electrochromic glass with a low-e coating on the surface facing the interior of the vehicle.
[0017] In another solution, EP 1 060 876 A2 describes a laminated glazing unit comprising an outer glass sheet, a sun protection stack comprising two silver layers arranged on face 2 (the face numbered from the outside inwards), a film of transparent PVB, a film of tinted PVB, and an inner glass sheet on which a low-e layer of fluorine-doped tin oxide is deposited.
[0018] Various combinations of the above systems (PVB and / or tinted glass) have also been proposed. This generally results in transmittance values T L It is 8-20%, of which the TTS factor is 20-35%.
[0019] Although such values are generally satisfactory, the solutions proposed so far are expensive and complex to implement and the price of the final glazing is relatively high, in particular due to the high cost of body-tinted glass and / or body-tinted PVB (or other interlayers). Body tinting refers to the introduction of a dye during the manufacturing phase of the product (glass or PVB) so as to be evenly distributed throughout the entire volume of said product, in contrast to clear glass or clear PVB which do not contain such dye.
[0020] However, as mentioned above, current solutions appear to be relatively expensive and complex to implement. They also result in a joint and non-selective reduction of TTS and TL. Furthermore, the selection of low TL and TTS values can usually only be achieved by increasing the glazing emissivity.
[0021] In order to obtain the best TL / TTS / emissivity compromise, glazings are sought that have an equally effective absorption profile, but are much less complex to manufacture than those of the prior art and in particular do not require the use of body-tinted glass or PVB. It is an object of the present invention to provide such glazings.
[0022] In particular, according to the present invention, preferably glazing units are sought which have the following specifications in common:
[0023] - a TTS of about 20% or less, or even less than 10%,
[0024] - less than 10% or even less than 5%, and even more preferably about 1 to 2% T L Light transmittance,
[0025] - Lowest possible emissivity ε n , and in particular an emissivity ε less than or equal to 30% n .
[0026] The problem behind the present invention is therefore to provide a glass which is easy and economical to manufacture, in particular which may not even contain body-tinted glass and / or body-tinted PVB, which can in particular be used as a vehicle roof and which satisfies the required compromise between TTS, TL and emissivity, in particular a visible light transmittance T of less than 10%, in particular of about 1 to 2%. L , and a TTS factor of less than 20%, and a low emissivity, which is in particular less than or equal to 30%.
[0027] The above-mentioned technical problem is solved by the laminated glazing according to the invention.
[0028] Such glazing comprises two glass sheets, at least a first glass sheet and a second glass sheet, bonded to one another by means of an interlayer, said glazing comprising a series of the following elements:
[0029] - the first glass sheet consists of transparent glass,
[0030] a multilayer of first layers which reflects infrared radiation, in particular infrared radiation from 780 nm and preferably solar infrared radiation from 780 nm to 2000 nm, said multilayer preferably being in contact with the inner surface of said first transparent glass sheet,
[0031] - said interlayer, preferably made of PVB, preferably deposited in contact with said stack of layers,
[0032] - said second glass sheet deposited in contact with said interlayer,
[0033] a multilayer of second layers in contact with the inner surface of the second transparent glass sheet, which multilayer of second layers reflects infrared radiation, in particular infrared radiation from 780 nm up to the thermal infrared (3 to 50 micrometers),
[0034] - a polymer layer, preferably deposited directly on the stack of layers or via an agent promoting adhesion to said stack, said polymer layer comprising a colorant that absorbs light in the visible range (380 to 780 nm) and is substantially transparent to infrared radiation with a wavelength greater than 780 nm, said polymer layer preferably being in direct contact with the external environment (i.e. it is the last element in the series, without any glass sheet, layer or stack covering it).
[0035] The terms "exterior" and "interior" refer to the positioning of the glazing in the vehicle in which it is equipped.
[0036] According to the invention, the outer surface of the glass sheet is exposed (ie in direct contact with the air outside the vehicle).
[0037] Additional advantageous features of such glazings are given below, which can of course be combined with one another as appropriate:
[0038] - the dye exhibits an absorption spectrum between 380 and 2000 nm for a 40 micron layer in a (meth)acrylate polymer and at a concentration of 1 wt %, as measured by a Perkin-Elmer Lambda 950 spectrophotometer at 25°C, the absorbance averaged between 780 nm and 2000 nm being at most one third, and preferably at most one fifth, or even at most one seventh, of the absorbance averaged between 380 nm and 780 nm.
[0039] - The dye is black or substantially black.
[0040] - at 25°C, the average molar extinction coefficient (or molar absorbance) of the dye between 780 nm and 2000 nm is at most one third, and even more preferably at most one fifth, or even at most one seventh, the average molar extinction coefficient between 380 nm and 780 nm.
[0041] The molar extinction coefficient, also called molar absorptivity or molar absorptivity, characterizes the ability of a composition to absorb light. The Beer-Lambert law states that it does not depend on the concentration of the composition or the thickness through which the light passes, but rather on the nature of the solute (in this case the dye) and the solvent (in this case the matrix), the wavelength of the incident light, and the temperature. For the purposes of the present invention, the "average" molar extinction coefficient thus corresponds to the average value of said coefficient measured over the wavelength range considered.
[0042] The stack of infrared radiation reflecting layers is a stack comprising at least two functional layers based on silver, preferably at least 3 functional layers based on silver, separated by layers of dielectric material, in particular oxide or nitride.
[0043] The polymer layer comprises or preferably consists of a polymeric compound selected from (meth)acrylate compounds, which are preferably multifunctional and comprise at least two acrylate functional groups.
[0044] The polymer layer is obtained by crosslinking a polymerizable composition comprising a (meth)acrylate compound optionally containing a polyorganosiloxane group, a polymerization initiator and optionally an adhesion promoter, wherein the (meth)acrylate compound comprises a high-functionality (meth)acrylate compound:
[0045] - has at least four (meth)acrylate functional groups and represents, in increasing order of preference, at least 65%, at least 70%, at least 80%, at least 90%, at least 94% by weight relative to the total weight of the composition, or
[0046] - has at least five (meth)acrylate functional groups and represents, in increasing order of preference, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% by weight of the composition relative to the total weight of the composition.
[0047] - Preferably, the polymerizable composition comprises a high functionality (meth)acrylate compound having at least six (meth)acrylate functional groups and constituting, in increasing order of preference, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% of the composition.
[0048] The term "(meth)acrylate" is understood to mean either acrylate or methacrylate.
[0049] The (meth)acrylate functional group refers to an acrylate functional group (CH2=CH-COO-) or a methacrylate functional group (CH2=CH(CH3)-COO-).
[0050] The polymer layer is essentially of organic nature. It is obtained from a polymerizable composition. It results from the crosslinking of polymerizable organic compounds present in the polymerizable composition.
[0051] The (meth)acrylate compounds account by weight in increasing order of preference relative to the total weight of the polymer layer:
[0052] - at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95% and / or
[0053] - up to 99%, up to 98%, up to 97%, up to 96%, up to 95%.
[0054] The (meth)acrylate compound has a molecular weight or average molecular weight (hereinafter referred to as molecular weight) of 150 to 10,000 g / mol.
[0055] The (meth)acrylate compounds include high-functionality (meth)acrylate compounds. These high-functionality compounds are selected from esters of acrylic acid or methacrylic acid, which contain at least four, at least five or at least six (meth)acrylate functional groups in increasing order of preference.
[0056] The (meth)acrylate compound including the high-functionality (meth)acrylate compound has a molecular weight of 500 to 10,000, 800 to 5,000, 1,000 to 2,000 g / mol in increasing order of preference.
[0057] In an advantageous embodiment, the high-functionality (meth)acrylate compound has at least four (meth)acrylate functional groups, which constitute in increasing order of preference at least 65%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% by weight relative to the total weight of the polymer layer.
[0058] According to another advantageous embodiment, the high-functionality (meth)acrylate compound having at least five (meth)acrylate functional groups accounts for at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% by weight, relative to the total weight of the polymer layer, in increasing order of preference.
[0059] According to another advantageous embodiment, the high-functionality (meth)acrylate compound having at least six (meth)acrylate functional groups accounts for at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 94% by weight, relative to the total weight of the polymer layer, in increasing order of preference.
[0060] Advantageously, the (meth)acrylate compound a) comprises a high functionality (meth)acrylate compound having at least six (meth)acrylate functional groups and a molecular weight of 1000 to 2000 g / mol. An example is CN9010EU, a product sold by Sartomer, which is an aliphatic urethane-acrylate prepolymer having six (meth)acrylate functional groups and a molecular weight of 1450 g / mol.
[0061] According to an advantageous embodiment of the invention, the polymerizable composition has the following additional characteristics:
[0062] - it comprises at least one polymerization initiator, preferably a photoinitiator,
[0063] - the polymerization initiator accounts for 0.1 to 20% by weight, or 1 to 15% by weight, preferably 3 to 15% by weight and better still 4 to 8% by weight of the composition,
[0064] The (meth)acrylate compound is selected from monomers, oligomers, prepolymers or polymers comprising at least one (meth)acrylate functional group.
[0065] - the (meth)acrylate compound is selected from esters of acrylic acid or methacrylic acid containing at least two (meth)acrylate functional groups,
[0066] - the (meth)acrylate compound optionally comprises at least one aliphatic urethane-acrylic oligomer,
[0067] - the (meth)acrylate compound comprises at least one oligomeric or prepolymerized monomer which contains, in increasing order of preference, at least 2, at least 3, at least 4, at least 5 or at least 6 (meth)acrylate functional groups,
[0068] the polymerizable composition may additionally comprise at least one additive selected from plasticizers, absorbers, release agents, heat and / or light stabilizers, thickeners, or surface modifiers,
[0069] The sum of all additives is from 0 to 10% by weight, preferably from 0 to 5% by weight, or even from 0.5 to 2.5% by weight of the composition.
[0070] According to one advantageous embodiment, the polymerizable composition comprises at least one additional compound comprising a polyorganosiloxane group and at least two (meth)acrylate functional groups.
[0071] According to the present invention, polymerization initiators and compounds comprising polyorganosiloxane groups are not considered to be additives.
[0072] The additional compound containing polyorganosiloxane groups has, for example, a molecular weight of 500 to 10,000 g / mol. Advantageously, the additional compound has, in increasing order of preference, a molecular weight of 500 to 15,000, 1,000 to 10,000, 3,000 to 7,000 g / mol. The molecular weight can be determined by gel permeation chromatography.
[0073] The additional compound comprises 0.05 to 5 weight percent of the polymerizable composition.
[0074] The compound containing polyorganosiloxane groups accounts for 0.05 to 5%, 0.1 to 4%, 0.2 to 3%, 0.3 to 2%, 0.3 to 1.5% of the total weight of the organic protective layer in increasing order of preference.
[0075] The polyorganosiloxane group of the compound containing a polyorganosiloxane group consists of 2 to 1000 organosiloxane units. The polyorganosiloxane group may be part of the main chain of the compound or part of a side chain.
[0076] The compound containing polyorganosiloxane groups can be selected from modified polyorganosiloxanes containing multiple (meth)acrylate functional groups. This type of compound corresponds to a compound having at least two (meth)acrylate functional groups, which are introduced at any position of the polyorganosiloxane chain (or backbone), in particular on a side chain or at the end of the main chain. In this case, the compound containing polyorganosiloxane groups accounts for 0.05 to 1.5% by weight, 0.1 to 1% by weight, 0.2 to 0.7% by weight, 0.4 to 0.6% by weight of the composition in an increasingly preferred order. This type of compound is sold, for example, under the name Byk 3505.
[0077] The compound containing polyorganosiloxane groups can be selected from modified poly(meth)acrylates containing polyorganosiloxane groups and at least two (meth)acrylate functional groups. This type of compound is sold, for example, by Sartomer under the name CN9800 ("bifunctional aliphatic acrylate silicone oligomer"). In this case, the compound containing polyorganosiloxane groups accounts for 0.2 to 4% by weight, 0.4 to 3% by weight, 0.6 to 2% by weight, 0.9 to 1.6% by weight of the composition in an increasing order of preference.
[0078] The thickness of the polymer layer is from 0.1 to 25 μm, preferably from 0.1 to 20 μm, in particular from 0.2 to 10 μm, or even from 0.2 to 5 μm and very preferably from 0.5 to 3 μm.
[0079] - Colorant selected from Epolight sold by Epolin Compounds in the series, in particular compounds 7527B and Epolight 7527C.
[0080] -Colorant selected from Sudan Black ((2,2-dimethyl-1,3-dihydroperylene-6-yl)-(4-phenylazo-1-naphthyl)diazepine, C 29 H 24 N6, CAS 4197-25-5) or Nigrosine Solvent Black 5 (NigrosineSolvent black 5) (CAS 11099-03-9), and preferably Sudan Black
[0081] - The colorant represents 5 to 70% by weight of the polymer, preferably 10 to 60% by weight of the polymer and more preferably 20 to 50% by weight of the polymer.
[0082] The glass sheet has a thickness of 0.7 mm to 5 mm, preferably 1.6 mm to 3.1 mm.
[0083] The stack of layers is a thin layer system having a thickness of 0.5 to 100 nm, comprising one or more silver-based layers, preferably at least two silver-based layers, more preferably three silver-based layers, separated by dielectric layers.
[0084] The invention also relates to the use of a laminated glazing as described above as a roof, side window or rear window of a motor vehicle.
[0085] The invention also relates to a method for producing a glazing unit as described above.
[0086] More particularly, such a method for producing laminated glazing comprises the following steps:
[0087] - depositing a stack of infrared reflecting layers as described above on the inner surface of the first inner glass sheet by means of a vacuum sputtering technique,
[0088] - optionally, shaping the glass, such as bending or tempering,
[0089] - assembling a first glass sheet coated with said multilayer with a colored or colorless transparent thermoplastic interlayer, in particular PVB, and with a second colored or transparent glass sheet comprising, on its opposite face, a multilayer of infrared reflecting layers,
[0090] - degassing, during which the air trapped between the glass sheet and the thermoplastic interlayer is removed,
[0091] - heat treatment of the laminated glass under pressure and / or in vacuum at temperatures between 60 and 200°C,
[0092] - depositing on said stack a polymer layer comprising a colorant as described above, said colorant absorbing light in the visible range and being transparent to infrared light,
[0093] - Drying and / or curing of the polymer layer containing the colorant, in particular by UV treatment.
[0094] By way of non-limiting example and for a better understanding of the present invention, the following Figures 1 to 3 Three embodiments of a glazing unit 10 according to the invention are shown, viewed in cross section.
[0095] These embodiments are particularly suitable for automotive glass roof structures, but can also be used as rear windows, or even as side window glazing.
[0096] The glazing 10 according to the invention comprises a first transparent glass sheet 1, i.e. its bulk is untinted. In particular, such glazing is usually obtained by a float process. In particular, such untinted glass may have a T of at least 88%, and more typically about 90%.L Light transmittance.
[0097] The glazing 10 separates the interior 7 of the vehicle from the exterior 8 and can be Figure 1 The bend is shown in .
[0098] The glass sheet is preferably 1 mm to 8 mm thick, in particular 1.5 mm to 4 mm thick. In order to reduce weight, the individual glass sheets should achieve the best possible compromise between low thickness and high safety, in particular when the glazing is installed in a motor vehicle. Such a compromise can be achieved in particular with glass sheets having a thickness of 1.5 mm to 3.1 mm, for example 2.1 mm.
[0099] According to the invention, the outer surface of the glass sheet 1 is preferably bare, while a first stack 2 of selective infrared reflecting layers is deposited on the inner part of the sheet 1. Such stacks are well known and comprise in particular a combination of a layer based on a noble metal, preferably a layer based on silver, and a dielectric material, generally referred to as an interference layer. As is well known, these stacks consist of a series of layers of dielectric materials, such as oxides and / or nitrides, and of metal layers, including layers based on silver, whose "low-e" properties enable them to selectively reflect infrared light, in particular solar infrared (wavelengths from 780 nm to 2500 nm), and in particular to allow at least a portion of the visible light of the solar spectrum (wavelengths from 380 to 780 nm), and preferably more than 70% or even more than 80%, to pass, while minimizing the light reflection by means of the interference layer or one or more combinations of interference layers.
[0100] In particular, the stacks according to the invention are selected such that their resistance per square is less than 1.5 ohms per square, preferably even less than 1.2 ohms per square, or even less than 1.1 ohms per square. For example, the resistance per square can be measured using a device such as the SRM-14T from NagyMess Systems.
[0101] Such stacks may comprise up to a few dozen layers with a thickness of 1 to 30 nm and are currently deposited using sputtering techniques, typically magnetron-assisted sputtering techniques.
[0102] Preferred multilayers according to the invention comprise two and preferably three or even four silver-based layers.
[0103] Examples of such stacks are described in particular in the above-cited publications WI2005 / 051858A1, WI2013 / 104439 and WI2013 / 107983.
[0104] The inner glass sheet 1 with the stack 2 is then firmly bonded to the second glass sheet 4 via the interlayer 3 .
[0105] The interlayer 3 comprises at least one intermediate film of a transparent plastic material (i.e. to which no dye has been added in order to color it, that is to say to change its color or the amount of light passing through it). This intermediate film is melted in a known manner in an autoclave between the two glass sheets in order to bond them together. Polyvinyl butyral (PVB), which can also be sound-absorbing, has proven to be the most suitable material for such an interlayer 3 and is used in most cases with a thickness of 0.38 mm or 0.76 mm.
[0106] As an alternative to PVB, the present invention also allows the use of any other known material to form a fused interlayer between two glass sheets, for example thermoplastics such as ethylene vinyl acetate copolymer (EVA), polyurethane (PU) or polyvinyl chloride (PVC).
[0107] Alternatively, but less preferably, the PVB film can be replaced by a film consisting of a layer system comprising, for example, a polyethylene terephthalate (PET) support layer embedded between two PVB layers. In this way, a three-layer film is formed to bond the individual glasses 1, 4 into a laminated structure.
[0108] According to a preferred embodiment, the interlayer 3 is a polyvinyl butyral (PVB) film or an assembly of several polyvinyl butyral films of different hardness for sound insulation properties, as described, for example, in publication EP1800855.
[0109] according to Figure 1 In the first embodiment shown in FIG. 1 , the PVB is transparent, that is, it contains no dye and is substantially transparent to visible light. Figure 2 In the second embodiment shown in FIG. 1 , the PVB is body-dyed, ie, it absorbs at least a portion of visible light.
[0110] The second glass sheet 4 may be identical to or different from the first glass sheet, in particular in terms of thickness.
[0111] like Figure 1 As shown in , it also includes transparent glass. Or, as Figure 3 As shown in FIG, the glass is colored in its body, for example VG10 (Venus Grey 10 TM ).
[0112] The use of tinted PVB or tinted glass reduces light transmission through the glazing.
[0113] Above the second glass sheet is a second stack 5 of selective infrared reflecting layers, which may be the same as the first stack 2 or different.
[0114] On top of the stack of second layers, an additional layer 6 consisting of a layer of a polymer compound is deposited. Preferably, such a polymer may be or comprise a polymer of the (meth)acrylate type, in particular of the type described in publications WO2018 / 178559, WO2018 / 178547 or WI2018 / 115768, WO2020 / 016527, or even more preferably of the type described in application WO2020 / 016529 as described above.
[0115] According to the invention, the polymer layer 6 can advantageously be obtained from a liquid composition comprising a (meth)acrylate oligomer comprising at least one methacrylate functional group and preferably comprising a plurality of methacrylate functional groups. For example, the liquid composition can advantageously comprise at least one aliphatic acrylic oligomer, at least one polymerization initiator and a colorant.
[0116] According to the invention, the polymer layer 3 may advantageously be obtained, for example, from a liquid composition comprising a (meth)acrylate compound chosen from monomers, oligomers or polymers comprising at least one (meth)acrylate function and preferably several methacrylate functions.
[0117] For example, the liquid composition comprises at least one monomer or oligomer of the preferred multifunctional (meth)acrylate compound, at least one polymerization initiator, and a colorant.
[0118] Advantageously, the colorant is present in the initial composition (excluding solvent) in an amount ranging from 5% to 70% of the total weight of the polymer compounds present in the polymer compound layer, preferably from 20% to 50% of said total weight.The polymer layer 6 may also comprise an adhesion promoter for the stack 5 of layers.
[0119] The polymer layer 6 can be deposited on the stack of layers 5 by applying the above-mentioned liquid composition at room temperature, by roller coating, spraying, dipping, curtain coating or spraying, or by spin coating techniques.
[0120] The polymer layer 6 is then cured by drying at a temperature below 200° C., by UV cross-linking, or by electron beam.
[0121] The thickness of the dried and / or cured polymer layer 6 may be from 0.1 to 20 microns, typically from 0.5 to 3 microns.
[0122] According to a possible alternative, in particular if no adhesion promoter is present in the initial composition, the surface of the stack of layers on which the coloured polymer layer is deposited can be pretreated with an adhesion promoter.
[0123] According to the present invention, the polymer layer acts as a matrix for the dye (or colorant), which is specifically selected for its light absorption qualities in the visible light range (380-780 nm) and is also substantially transparent to near infrared rays, especially those from 780 to 2000 nm.
[0124] Visible light absorber means that the dye absorbs most, such as at least 60% or even greater than 70% or even greater than 80%, or even substantially all visible light. Similarly, infrared transparent or substantially infrared transparent means that the dye allows most, such as at least 60% or even greater than 70, 80 or even 90% of infrared light, or even substantially all infrared light to pass through.
[0125] According to an advantageous embodiment, such a colorant is from Epolight sold by the company Epolin. series of compounds, in particular compounds 7527B and Epolight 7527C (https: / / www.epolin.com / epolight-voirt-dyes-for-solvent-based-systems / ).
[0126] The following Figure 4 The absorption spectrum of Epolight 7527C at a concentration of 1% by weight in an acrylate layer is shown as an example. The absorbance measured between 380 and 780 nm is 0.79, and the absorbance measured between 780 and 2000 nm is 0.08.
[0127] According to another possibility, a dye of the Sudan type may be chosen, in particular the Sudan Black B dye, the structural formula of which is given below:
[0128]
[0129] Of course, the invention is not limited to such compounds, and any dye having a low infrared absorption coefficient between 780 nm and 2000 nm and a high absorption coefficient in the visible range in its matrix can be used according to the invention. In principle, the dye used is black, but dyes can also be used which do not absorb all visible light, but at least 60%, at least 70% or even at least 80% of the visible light and thus exhibit a slight but dark coloration.
[0130] Advantageously, the dye is selected to meet the above absorbance and extinction coefficient criteria.
[0131] Used as laminated glazing, in particular for automotive glass roof applications, the glazing according to the invention solves the above technical problems due to its special structure. In particular, it provides the following advantages:
[0132] - low cost of the materials used in its composition, since it does not contain the most expensive elements present in existing structures (in particular, no initial body-tinted PVB, no body-tinted glass), and therefore the manufacturing cost is low. In addition, the liquid deposition used according to the invention is generally inexpensive due to its high line speed, and the dyes used are commercially available and inexpensive;
[0133] - the possibility of adjusting the light transmittance of the glazing by adjusting the weight concentration of the dye in the polymer layer to values of up to 5% or even 10% of the total weight of said layer;
[0134] -Optimal solar control properties of laminated glass:
[0135] a) due to the presence of the following stack on the first glass sheet, which reflects the solar infrared but allows most of the radiation in the visible range to pass,
[0136] b) Due to the nature and positioning of the colorant in the glazing: A large part of the infrared part of the solar spectrum is reflected by the stack of layers, and then the remaining radiation, which mainly comprises the visible part of said radiation, is partially absorbed by the layer comprising the colorant, depending on the concentration of the colorant in said layer. Since the infrared radiation cannot reach said layer, no additional heating of the glazing and thus of the vehicle interior occurs. The glazing therefore has a low TTS value. Similarly, in winter, the glazing provides good insulation for the passenger compartment due to the presence of the infrared reflecting coating.
[0137] The stack of layers and the dye concentration are advantageously selected in combination to allow a sufficiently large amount of light to pass through in order to adequately illuminate the interior space and thereby maintain visual comfort and a pleasant feel.
[0138] Exemplary embodiments of glazing according to the invention are given below:
[0139] A-Manufacturing the structure according to the invention:
[0140] Prepare as above combined Figure 1 Sample A of the described structure, whose dimensions are 10×10 cm 2 .
[0141] Sample A was obtained as follows:
[0142] - Using magnetron assisted sputtering technology, the stack of layers is coated by a filing company under the name The first 2.1mm thick clear glass (TL The stack comprises three silver layers and is described in Example 14 of publication WI2005051858. Its resistance per square is 1.0 ohm / square, measured using a device such as SRM-14T from Nagy Mess Systems.
[0143] A 0.76 mm thick transparent PVB film (produced by Eastman under the trademark A first glass sheet coated with an interlayer (sold) is placed on the first glass sheet coated with the interlayer, and a second transparent glass sheet having a second interlayer identical to the first interlayer is attached to the interlayer so that the laminated glazing is close to the second interlayer, wherein the second interlayer is located on the face of the second glass sheet opposite to the face bonded to the PVB. The assembly is placed in an autoclave at 130° C. and a pressure of 12 bar for 30 minutes.
[0144] On the second stack of thin layers, a liquid composition having the following composition is deposited:
[0145] A hexafunctional aliphatic acrylate oligomer having a molecular weight of 1450 g / mol (hereinafter referred to as 6-functional acrylate oligomer), sold by Sartomer under the name CN9010EU.
[0146] - a modified polyorganosiloxane comprising various (meth)acrylates having a molecular weight of 6,500 g / mol, sold under the name Byk 3505 by Byk.
[0147] - an adhesion promoter consisting of triacrylate monomers of the acid type sold under the name SR9051 by Sartomer.
[0148] - the photoinitiator sold under the name Speedcure 500 by Lambson.
[0149] The following table shows the different proportions of the four ingredients in the initial mixture:
[0150] [Table 1]
[0151] formula Product Name Weight Percent Acrylate oligomer CN90 10EU 94 Polysiloxane Byk 3505 0.5 Adhesion promoter SR9051 0.5 Photoinitiator Speedcure 500 5
[0152] The four components, precursors of the initial polymer matrix, were dispersed in methyl ethyl ketone (MEK) used as solvent.
[0153] Prior to the solvent removal step, according to the invention, the above-mentioned Epolight 7527C dye was additionally added to the initial solution.
[0154] A mixture containing 12 wt % of the precursor mixture and 5 wt % of the dye was prepared with 83 wt % of MEK.
[0155] The resulting liquid composition was filtered through a 0.2 micron diameter PTFE filter and then spin-coated onto a glass substrate until it reached a thickness of 5 microns.
[0156] UV irradiation (UV-B dose is approximately 280 mJ / cm 2 The layer thus obtained was cured at a rate of advance of 10 m / min. The thickness of the dry dyed layer was approximately 1 μm.
[0157] B- Characterization of the glazing according to the invention:
[0158] Optical characterization of the glazings as described above was performed using a Lambda 900 spectrophotometer from Perkin Elmer.
[0159] According to ISO9050 (2003) the light factor (T L and R L ).
[0160] Total Solar Transmittance (TTS) is measured according to ISO 13837 using the "A" AM 1.5 convention.
[0161] The emissivity is calculated according to the criteria defined in the international standard NF EN 12898: 2001. For the purposes of this example, an emissivity of up to 30% is considered satisfactory and above this value the material can no longer be used satisfactorily as insulating glass.
[0162] Table 2 below shows the main chromaticity data of the glazing according to the invention when the Epolight 7527C dye is used:
[0163] [Table 2]
[0164]
[0165] The dyeing layer also effectively reduces the light transmittance T L , T was measured at 1% for a 30% concentration of colorant L The resulting laminated glass appears deep blue when viewed from inside the cabin.
[0166] The measured TTS is less than 20%, which is substantially equal to or even lower than the values obtained with the prior art configurations described previously and applied based on PVB and / or tinted glass.
[0167] According to the invention, by acting on the concentration of the coloring agent, it appears possible to adjust the light transmittance and the total energy transmittance of the glazing down to a value of up to 1% T L and below 10% TTS level.
Claims
1. A laminated glazing (10) comprising two glass sheets bonded to each other by means of an interlayer (3), the glass sheets comprising at least a first glass sheet (1) and a second glass sheet (4), the glazing comprising a series of the following elements: - the first glass sheet (1), which consists of transparent glass, a multilayer (2) of first layers reflecting infrared radiation, preferably in contact with the inner surface of said first transparent glass sheet (1), - said interlayer (3), preferably made of PVB, preferably deposited in contact with said stack of layers, - the second glass sheet (4), a multilayer (5) of a second layer reflecting infrared radiation in contact with the inner surface of said second transparent glass sheet (4), a polymer layer (6) comprising a colorant absorbing light in the visible range between 380 and 780 nm and transparent to infrared radiation with a wavelength greater than 780 nm, said polymer layer preferably being in direct contact with the external environment.
2. The laminated glazing according to claim 1 , wherein the absorbance of the dye averaged between 780 nm and 2000 nm is at most one third of the absorbance averaged between 380 nm and 780 nm, measured by a Perkin-Elmer Lambda 950 spectrophotometer for a 40 micrometer layer in a (meth)acrylate polymer and at a concentration of 1% by weight, over the absorption spectrum between 380 and 2000 nm. 3 . The glazing according to claim 1 , wherein the average molar extinction coefficient of the dye between 900 nm and 2000 nm at 25° C. is at most one third of the average molar extinction coefficient between 380 nm and 780 nm.
4. The laminated glazing according to claim 1 , wherein the stack of layers reflecting infrared radiation is a stack of at least two, and preferably at least three, functional layers based on silver, separated by layers of dielectric material, in particular layers of oxides or nitrides. 5 . The laminated glazing according to claim 1 , wherein the layer comprises or preferably consists essentially of a polymeric compound selected from (meth)acrylate compounds, which are preferably multifunctional and comprise at least two acrylate functional groups.
6. Laminated glazing according to claim 1 , wherein the polymer layer is obtained by crosslinking a polymerizable composition comprising a (meth)acrylate compound, optionally a polyorganosiloxane group, optionally a polymerization initiator, optionally an adhesion promoter to the stack, wherein the (meth)acrylate compound comprises and is preferably a high-functionality (meth)acrylate compound: - has at least four (meth)acrylate functional groups and accounts for at least 65% by weight relative to the total weight of the organic protective layer, or - has at least five (meth)acrylate functional groups and accounts for at least 50% by weight relative to the total weight of the organic protective layer. 7 . The laminated glazing according to claim 1 , wherein the polymer layer has a thickness of 0.1 to 20 μm, in particular 0.5 to 3 μm.
8. Laminated glazing according to any one of the preceding claims, wherein the colorant is chosen from the group consisting of Epolight sold by the company Epolin. Compounds in the series, in particular compounds 7527B and Epolight 7527C.
9. The laminated glazing according to claims 1 to 7, wherein the colorant is selected from Sudan Black (CAS4197-25-5) or Nigrosine Solvent black 5 (CAS11099-03-9), and Sudan Black is preferred 10 . The laminated glazing according to claim 1 , wherein the colorant represents 5 to 70% by weight of the polymer layer, preferably 20 to 50% by weight of the polymer layer.
11. Laminated glazing according to one of the preceding claims, wherein the second glass sheet (4) is made of clear glass and the interlayer (3) is body-tinted and consists in particular of tinted PVB.
12. Laminated glazing according to any one of claims 1 to 10, wherein the second glass sheet (4) is made of body-tinted glass and the interlayer (3) is colorless, in particular consisting of untinted PVB.
13. The laminated glazing according to claim 1, wherein the second glass sheet (4) is made of transparent glass and the interlayer (3) is colorless, in particular made of untinted PVB.
14. Laminated glazing according to any one of the preceding claims, characterized in that The glass sheet has a thickness of 0.7 to 5 mm, and preferably 1.6 to 3.1 mm.
15. Use of the laminated glazing according to one of the preceding claims as a rear window, side window or roof window of a motor vehicle.